Impact of Economic Crisis to Family Planning Realination on Poor Household in Banjarsari District, Surakarta - Wahyuni Apri Astuti; P Priyono; Retno Woro Kaeksi; Muhammad Musiyam (Forum Geografi, 2001)
This study is carried out in Nusukan, Banjarsari, Surakarta. The problems that are related to economic crisis in Indonesia are the supply of contraception, the weakening of people purchasing power so they influence the realization of family planning program. The goals of the study are: to know the supply of contraception for poor household, to study the influence of the effect of economic crisis for the participant of family planning, to study the change of birth control and its effective strategy and to know the quality of family planning service. The data are collected using observation, and questionnaire. The study takes the area in which it has more productive couple, the percentage of poor families and the prosperous families I that belong to productive couple whose age 20 to 49 years old, at least they have two children, and participant of family planning or ever followed it. The result of the study shows that 82% respondents can get contraception easily before and at economic crisis. It is one of the important factors, for which the participant of family planning is still high. Although the economic crisis influences the price of contraception and family Income, it does not affect the participant of family planning. 87% respondents participate actively the family planning. This shows that the people have realized the importance of family planning program. There is an impact of economic crisis for the change of the ways of birth control. 38% respondents have changed over their strategy from modern to traditional contraception and the contrary, and from modern contraception to the other one. Some of them are abstention. The level of the people adaptation is high enough. They use various ways to prevent of being pregnant. 92% respondents do not want to be pregnant. If it happens an unwanted pregnancy, 15% of the respondents will abort their pregnancy. This is the challenge for the officers and the government to supply safe and accurate contraception and to give clear explanation about the effect of abortion from healthy and religious aspect. The service of family planning by the government and private institution is good enough (81%). Respondents can get contraception (especially tablet) easily; cheap and free of charge, but the other ones such as spiral is more difficult because it is more expensive and limited.